Representation of analytic functions by generalized series of exponents in unbounded convex domains - Krutigolova, Ye. K. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We establish conditions for the representation of functions f(z) analytic in unbounded convex domains D and continuous in \(D\) via series of the form \(olimits_n = 1^∞ P_n ( z ) e^λ _n z \) .